Pengaruh Motivasi Wisata Dan Citra Destinasi Terhadap Keputusan Berkunjung di Museum Angkut Batu (Studi Kasus pada Mahasiswa FEB Universitas Islam Malang Angkatan 2016) - Galang Jalu Tanaya; N Rachma; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to examine and analyze the partial influence of tourism motivation on visiting decisions, the partial influence of destination image on visiting decisions, and the simultaneous influence of tourism motivation, destination image on visiting decisions. The population of the study were students of the Islamic University of Malang class of 2016 who had visited the Angkut Batu Museum whose numbers were unknown, so the sample calculation using the Malhotra method resulted in 100 samples. The data analysis technique used instrument test, normality test, multiple linear regression analysis, classical assumption test, and hypothesis test using SPSS 25.0 multiple regression analysis. The results of this study are tourism motivation and destination image have a significant effect on the decision to visit the Museum Angkut Batu either partially or simultaneouslKeyword : tourism motivation, destination image, visiting decision